Comparison of Mixed and Choice Feeding of Whole Wheat (Triticum aestivum) on the Performance of Commercial Broilers - Bhagora, Nikesh J; Savaliya, Fulabhai P; Patel, Atul B; Lonkar, Vijaysinh D (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Wheat is the cereal grain of choice for Whole Grain Feeding (WGF) in poultry, despite the fact that globally maize is the most commonly used cereal grain. In this context, in the present study  feeding of whole wheat to commercial broilers with two types of feeding systems were used ie.  mixed and choice feeding systems of wheat with different levels of replacement with maize by 20, 40, 60, 80 and 100%. The body weight and body weight gain of birds fed with 20% and 40% choice feeding of wheat was found to be the highest (p
Keywords: Choice feeding; Commercial broilers; Economics; Mixed feeding; Production performanc; Whole wheat